Analysis of Policy Evaluation and Model of ASN Management Improvement in terms of Planning, Recruitment, and Competency Development Aspects - Robby Kurniawan; Aries Djaenuri; Hadi Prabowo; Sampara Lukman (GoAcademica Research & Publishing, 2020)
This study aims to analyze the evaluation of ASN management policies at the Ministry of Transportation and the provincial government of DKI Jakarta and the appropriate model for improving ASN management in planning, recruitment, and potential development. The approach used in this study is to use action research-based Soft Systems Methodology (SSM) as a research method with systems thinking approach. This research method's selection was carried out considering that ASN management is a Human Activity System with various problems involving many agencies. There are multiple laws and regulations used. The results showed that the evaluation analysis from the planning aspect showed that the policies, their formulation, and their dissemination had been carried out well; The recruitment aspect indicates that there is still something that needs to be addressed, especially in the recruitment of CPNS, PPPK, and open selection of positions; Aspects of competency development receive greater attention, especially in terms of improving performance, cost efficiency and achieving organizational goals. This study also develops concepts to improve ASN management in the form of a framework that includes: foundational theories, foundational theory & empirical facts as fundamental to formulate research interest, and research contributions.